2021
DOI: 10.3897/pharmacia.68.e64422
|View full text |Cite
|
Sign up to set email alerts
|

The supplementary effects of omega-3 fatty acid alone and in a combination with vitamin D3 on serum leptin levels: A randomized clinical trial on men and women with vitamin D deficiency

Abstract: Purpose: This randomized clinical trial (RCT) was designed to assess the effect of VD3, n-3FA, and their combination on serum leptin levels in people with vitamin D deficiency (VDD). Subjects and methods: One hundred and forty six participants, were randomly assigned into four groups supplemented with the dose of 50,000 IU VD3 taken weekly (D), 300 mg n-3FA taken daily (Om), and their combination (D+Om) or control (C) for eight weeks. Fasting baseline and follow-up (10 weeks; 8 weeks supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…, 2017; Rajabi-Naeeni et al ., 2020) included only women, and the remaining four studies (Lee et al. , 2015; Abu-Samak et al. , 2021; Kouchaki et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…, 2017; Rajabi-Naeeni et al ., 2020) included only women, and the remaining four studies (Lee et al. , 2015; Abu-Samak et al. , 2021; Kouchaki et al.…”
Section: Resultsmentioning
confidence: 99%
“…The full texts of the remaining 14 articles were then examined, and 8 of them were excluded for not reporting the desired data or not being randomized. Eventually, this systematic review and meta-analysis comprised six RCTs (Jamilian et al, 2017;Lee et al, 2015;Abu-Samak et al, 2021;Kouchaki et al, 2018;Rajabi-Naeeni et al, 2020;Talari et al, 2019). A flow diagram of the study selection is shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations